Performa Ayam Broiler yang Diberi Ransum Mengandung Bungkil Biji Jarak Pagar (Jatropha curcas L.) Hasil Fermentasi Menggunakan Rhizopus oligosporus - . Sumiati; . Farhanuddin; W Hermana; A Sudarman; N Istichomah; A Setiyono (Faculty of Animal Science, Bogor Agricultural University, 2011)
Jatropha curcas meal (JCM) contains high crude protein (58%-60%), but it can not be used properly because of anti-nutritional contents known as curcin and phorbolesther. These components interferes protein metabolism and body protein synthesis. This study was conducted to evaluate the effect of feeding fermented JCM using Rhizopus oligosporus on broilers' performances. Ninety six of day old chicks of Ross strain broiler (initial body weight 45.6±1.7 g) were used and reared for five weeks. The treatments were: R0 (diet without JCM), R1 (diet contained 3% fermented JCM), R2 (diet contained 6% fermented JCM) and R3 (diet contained 9% fermented JCM). A completely randomize design with 4 treatments and 4 replications was assigned in this experiment. The data were analyzed using analysis of variance (ANOVA). The results indicated that feeding fermented JCM at the level of 3% to 9% in starter and grower-finisher broilers highly significant reduced (PR. oligosporus indicated no effective detoxification process in relation to the improvement of broiler performances.